The relationship between the circular economy, green growth, and the green economy in Vietnam - Nguyen, Thùy Linh; Nguyen , Văn Mạnh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This article focuses on the relationship between the circular economy, green growth, and the green economy in Vietnam. The results indicate that the circular economy model, with resource optimization and waste minimization, plays a crucial role in promoting green growth and advancing towards a sustainable green economy. The article uses data from the WB (2024) to analyze the current situation, challenges, and propose specific solutions for Vietnam in implementing the circular economy and green growth.